1999
DOI: 10.1080/10473289.1999.10463889
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Factors Influencing Winter Primary Particle Sampling and Interpretation

Abstract: Aerosol samplers collect material that is locally generated as well as that transported from upwind; knowing the extent of the area from which the sample is drawn is necessary for proper interpretation of sampler data. The U.S. Environmental Protection Agency (EPA) PM 2.5 monitoring guidelines recognize a conceptual hierarchy of sampler spatial representation, but provide no objective measures of a site's spatial representativeness. A case study of a sampler tributary area in central California provides insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The detailed requirements for the location of individual types of monitoring stations for particulate matter (and other criterion pollutants) have been specified in Directive 2008/50/EC (Annex III). In addition to meteorological conditions, seasonal changes or long-range transport of air pollutants [66][67][68][69], local conditions may also affect the measurement point [1,70,71]. For a specific urban area, a uniform distribution of PM 2.5 , PM 10 or PM 2.5-10 is often only a guess, usually due to the limited availability of measuring equipment [4,34,35,57,72].…”
Section: Localization Of Monitoring Sites and The Spatial Distributiomentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed requirements for the location of individual types of monitoring stations for particulate matter (and other criterion pollutants) have been specified in Directive 2008/50/EC (Annex III). In addition to meteorological conditions, seasonal changes or long-range transport of air pollutants [66][67][68][69], local conditions may also affect the measurement point [1,70,71]. For a specific urban area, a uniform distribution of PM 2.5 , PM 10 or PM 2.5-10 is often only a guess, usually due to the limited availability of measuring equipment [4,34,35,57,72].…”
Section: Localization Of Monitoring Sites and The Spatial Distributiomentioning
confidence: 99%
“…For a specific urban area, a uniform distribution of PM 2.5 , PM 10 or PM 2.5-10 is often only a guess, usually due to the limited availability of measuring equipment [4,34,35,57,72]. The impact is particularly strong for sources within a radius of around 10 km (neighbourhood scale) and very weak for the entire region [70]. Typically, the spatial distribution of PM 2.5 is relatively homogeneous; only in the vicinity of the PM emission source the concentrations might be elevated in relation to the background concentrations [46,71].…”
Section: Localization Of Monitoring Sites and The Spatial Distributiomentioning
confidence: 99%
“…18 Several other studies in European 26 and American 9,23,32-35 cities have reported homogeneous PM 2.5 levels, whereas for the coarse fraction and PM 10 , more withincity variability was observed. 23,36,37 However, two recent studies reported within-city variability for both PM 2.5 and PM 10 in California 38 and Canada.…”
Section: Spatial Distribution Of Ambient Pm 25mentioning
confidence: 99%
“…Nitrate compounds, particularly secondary nitrate compounds formed in photoreactions, have been identi ed as major constituents of central and southern California aerosols (VanCuren 1999;Kim et al 1999). Therefore it was prudent to assume that a speci c gravity representative of ammonium compounds, 1.7, would be appropriate for some part of the submicrometer aerosol.…”
Section: Choice Of Specific Gravitymentioning
confidence: 99%